Analysis of the Role of Social Media and Consumer Preferences in Increasing Online Buying Interest of Students of the Faculty of Economics and Business, Udayana University - I Gusti Ayu Ngurah Sindi Sasmita; I Gede Krishna Wiradinatha (The Journal of Management, Digital Business, and Entrepreneurship, 2025)
This study aims to analyze the influence of social media and consumer preferences on online buying interest of Package 7 students, Faculty of Economics and Business, Udayana University. The research method used is a quantitative approach with a Likert-scale questionnaire instrument, as well as multiple linear regression analysis. The F test results show a significance value of 0.006 which is smaller than 0.05, so the regression model is declared feasible to use. These results prove that social media variables and consumer preferences simultaneously have a significant effect on online buying interest. Thus, the research model can explain the relationship between variables empirically and is relevant to current digital phenomena. The t-test results show that social media variables have a significant effect with a negative coefficient direction, which means that exposure to certain social media actually reduces online buying interest if not managed properly. Conversely, consumer preferences have a significant effect with a positive coefficient direction, indicating that the stronger consumer preferences, the higher the interest in buying online. The R Square value of 0.387 indicates that the two independent variables are able to explain 38.7% of the variation in online purchase intention. The remaining 61.3% is influenced by other factors outside the model, such as price, product quality, and promotion. This research provides theoretical and practical contributions in digital marketing strategies, especially among the younger generation.